Przestrzeń międzygeneracyjna – relacje młodzieży z rodzicami - Karmolińska-Jagodzik , Ewa (Studia Edukacyjne, 2018)
This article is an attempt to theoretically capture the concept of space in the context of intergenerational relations, in particular in the field of young people’s relations with their parents. The theoretical approaches undertaken induce an exemplification of the concept of space and its constituent elements, which are distinguished in intergenerational relations. The concept of space is depicted in the notion of social sciences. Intergenerational relations take place in a specific type of space, which consists of individual segments. Taking into account family relationships and ties encourages reflection on the uniqueness and diversity of aspects related to intergenerational relationships between young people and their parents.